Leverage, Capital Intensity, Profitability, and Tax Aggressiveness: The Role of Corporate Social Responsibility Moderation - Hendrawan Hendrawan; Estralita Trisnawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aimed to analyze the influence of leverage, capital intensity, and profitability on tax aggressiveness with corporate social responsibility as a moderating variable. The object of this research is consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The method used in this study was quantitative with a purposive sampling approach to obtain secondary data from the company's annual report and sustainability report. Data analysis was carried out using multiple linear regression and moderated regression analysis (MRA). The results of the study showed that leverage and profitability had a positive effect on tax aggressiveness, while capital intensity did not have a significant effect. Furthermore, corporate social responsibility has been shown to negatively moderate the relationship between leverage and profitability to tax aggressiveness, but does not moderate the relationship between capital intensity and tax aggressiveness. These findings indicate that a commitment to social responsibility can dampen companies' tendency to aggressively evade taxes. This research made an important contribution to the development of the tax accounting literature as well as practical implications for policymakers and corporate management in designing ethical and sustainable tax strategies.